2009
DOI: 10.1002/jcu.20617
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intima‐media thickness and cerebrovascular reactivity in long‐term type 1 diabetes mellitus

Abstract: Our results refer to early macro- and microangiopathic involvement of the cerebral vessels, which develop in parallel with angiopathies of the other organs, such as nephropathy and retinopathy. Further prospective studies are needed to clarify the role of these macro- and microangiopathic changes in the development of cerebrovascular complications in patients suffering from DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…As a consequence, sudden intraoperative changes of cerebral perfusion pressure and/or carbon-dioxide concentration may challenge the autoregulatory and metabolic regulatory responses and thus may result in critical brain tissue oxygenation. In line with our observations previous studies in humans also demonstrated that sevoflurane at ≤1 MAC concentrations do not affect cerebral autoregulation (2,15,16). In a very recent study Sperna Weiland and co-workers found that sevoflurane does not affect the already impaired cerebral autoregulation in diabetic patients at clinicially applied doses (17).…”
Section: Discussionsupporting
confidence: 92%
“…As a consequence, sudden intraoperative changes of cerebral perfusion pressure and/or carbon-dioxide concentration may challenge the autoregulatory and metabolic regulatory responses and thus may result in critical brain tissue oxygenation. In line with our observations previous studies in humans also demonstrated that sevoflurane at ≤1 MAC concentrations do not affect cerebral autoregulation (2,15,16). In a very recent study Sperna Weiland and co-workers found that sevoflurane does not affect the already impaired cerebral autoregulation in diabetic patients at clinicially applied doses (17).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, whyle using some agents, direct cerebral effect has also to be taken Previous reports indicated that sevoflurane between 0.5-1.0 MAC has minimal direct vasodilatory effect on the brain arteries (8,9)and has no systemic hemodynamic effects (cardiac contractility and/or peripheral vascular resistance) at the most frequently used 1 MAC sevoflurane (10). In the present study, during the induction phase, the combination of propofol-fentanyl-rocuronium and adding sevoflurane resulted in a decreased mean arterial pressure (mainly due to the decrease of the Previously it has been demonstrated that cerebral autoregulation and reactivity of the cerebral vessels to induced hypocapnia may be impaired in patients with certain underlying diseases, such as hypertension and diabetes mellitus (11)(12)(13)(14). As a consequence, sudden intraoperative changes of cerebral perfusion pressure and/or carbon-dioxide concentration may challenge the autoregulatory and metabolic regulatory responses and thus may result in critical brain tissue oxygenation.…”
Section: Discussionmentioning
confidence: 50%
“…An increased cIMT was observed not only in long-standing type 2 diabetic but also in newly detected type 2 diabetic patients (5,8). In type 1 diabetes mellitus (T1DM) cIMT was found to be thicker already in children, adolescents and young adults (3,4,13,20,29,33,39). Increased cIMT within the normal upper limit shows that young women with pGDM have an early sign of vessel involvement (1,9,42).…”
Section: Imtmentioning
confidence: 95%